2006
DOI: 10.1557/jmr.2006.0326
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of 5:3 plates in RE5(SixGe1-x)4 alloys

Abstract: Studies of RE 5 (Si x Ge 1-x ) 4 alloys, where RE equals rare earth, have revealed a second-phase having a thin-plate morphology in essentially every alloy examined, independent of exact composition and matrix crystal structure. Identified as having a composition approximating Gd 5 (Si x Ge 1-x ) 3 and a hexagonal crystal structure in the Gd-based system, it has been suggested that the observed thin-plate second phases seen in this family of rare earth alloys are all most likely of the form RE 5 (Si x Ge 1-x )… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…formation are yet unknown. The high degree of stability noted for the plates [85] suggests a strong kinetic driving force in much the same way martensitic transformations occur in opposition to equilibrium thermodynamic considerations. Further study of the 5:3 thin plates to define their formation temperature and range of stability is needed if one is to manipulate and control the structure.…”
Section: Motivation Of the Study And Dissertation Organizationmentioning
confidence: 95%
See 1 more Smart Citation
“…formation are yet unknown. The high degree of stability noted for the plates [85] suggests a strong kinetic driving force in much the same way martensitic transformations occur in opposition to equilibrium thermodynamic considerations. Further study of the 5:3 thin plates to define their formation temperature and range of stability is needed if one is to manipulate and control the structure.…”
Section: Motivation Of the Study And Dissertation Organizationmentioning
confidence: 95%
“…The precipitation of 5:3 plates appears relatively independent of the initial crystal structure and composition of the parent matrix [79,82]. Somewhat surprising was that alloy compositions specifically chosen in an attempt to avoid 5:3 formation still possessed 5:3 plates whenever the 5:4 phase was present, pointing to an unusual stability of the 5:3 plates within a 5:4 matrix [85].…”
Section: The R 5 (Si X Ge 1-x ) 3 Family Of Intermetallic Compoundsmentioning
confidence: 99%
“…Extensive research on the magnetic properties of RE 5 (Si x Ge 1Àx ) 4 (hereafter referred to as "5:4" compounds), has resulted in the microstructures of this 5:4 system capturing the attention of researchers [5e11, 14,15]. The earliest studies [5] reported the existence of linear features visible on the surface of Gd 5 Si 4 , Gd 5 Si 2 Ge 2 , and Gd 5 Ge 4 samples.…”
Section: Introductionmentioning
confidence: 99%
“…Ugurlu et al [14] investigated the persistence of the 5:3 plates in Gd 5 Si 2 Ge 2 under thermal cycling and concluded that the 5:3 plates are stable in the temperature range À70 C to 850 C. Somewhat surprising was that alloy compositions specifically chosen in an attempt to avoid 5:3 formation still possessed 5:3 plates whenever the 5:4 phase was present, pointing to an unusual stability of the 5:3 plates within a 5:4 matrix. However, that study was limited in scope with an emphasis being on the cycling of the temperature, rather than on long-term stability at higher temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…formation are yet unknown. The high degree of stability noted for the plates [85] For instance, magnetic ordering occurs simultaneously with the crystallographic change in Gd 5 Si 2 Ge 2 [13], ferromagnetic ordering accompanied by a crystal rearrangement can be triggered by a magnetic field in Gd 5 Ge 4 [14], and a pressure-induced magneto-structural coupling is present in Tb 5 Si 2 Ge 2 [15]. Conversely, the compound Er 5 Si 4 exhibits an interesting decoupling of the magnetic and structural transformations [16 -17].…”
Section: Motivation Of the Study And Dissertation Organizationmentioning
confidence: 91%